Creating metacognitive environments in primary school RE classrooms - Larkin, Shirley (Journal of beliefs and values, 2014)
Recent reports on Religious Education (RE) in England and Wales highlight the need for guidance on pedagogy and learning. The RE-flect project addressed this by promoting the creation of metacognitively oriented learning environments in primary school RE classrooms. Six primary school teachers and 160 pupils (eight to 10 years of age) took part in the second year of this two year project. Meta-thinking, worldview and resources zones were created in each classroom. Attainment in RE and pupil perceptions of the learning environment were measured. Data from classroom observations, Worldview Profiles (WVP), and pupil and teacher interviews were analysed qualitatively. Results show an overall increase in attainment; a positive change in pupil perceptions of the learning environment; and the ability of pupils to reflect on and articulate their worldviews. Implications for RE curricular and pedagogy are discussed.